Search for pulsation among suspected A-type binaries and the new multiperiodic δ Scuti star HD 217860 - Frémat, Y.; Lampens, P.; van Cauteren, P.; Kleidis, S.; Gazeas, K.; Niarchos, P.; Neiner, C.; Dimitrov, D.; Cuypers, J.; Montalbán, J.; De Cat, P.; Robertson, C. W. (2007)
Context: In the H-R diagram, the intersection of the main sequence and the classical Cepheid instability strip corresponds to a domain where a rich variety of atmospheric phenomena are at play (including pulsation, radiative diffusion, convection). Main-sequence A-type stars are among the best candidates to study the complex interplay between these various phenomena. Aims: We have explored a sample of suspected A-type binaries in a systematic way, both spectroscopically and photometrically. The sample consists of main-sequence A-type stars for which the few existing radial velocity measurements may show variability, but for which other essential information is lacking. Due to their location in the H-R diagram, indications of pulsation and/or chemical peculiarities among these suspected binary (or multiple) systems may be found. Methods: High-resolution spectroscopy obtained with the ELODIE and MUSICOS spectrographs was used in combination with a few nights of differential CCD photometry in order to search for pulsation(s). In order to search as well for chemical peculiarities or for possible hidden component(s), we derived the atmospheric stellar parameters by fitting the observed spectra with LTE synthetic ones. Results: Of the 32 investigated targets, eight are spectroscopic binaries, one of which is a close binary also showing eclipses, and three have been identified as δ Scuti pulsators with rapid line-profile variations. Conclusions: Among the latter stars, HD 217860 reveals interesting multiperiodic photometric and spectroscopic variations, with up to eight frequencies common to two large photometric data sets. We suggest that at least one radial overtone mode is excited among the two most dominant frequencies, on the basis of the computation of the pulsation constants as well as of the predicted frequencies and the expected behaviour of the amplitude ratio and the phase difference in two passbands using adequate theoretical modelling. We furthermore found evidence for a strong modulation of the amplitude(s) and/or the (radial) frequency content of this intriguing δ Scuti star. This work is based on spectroscopic observations made at the Haute-Provence Observatory (OHP), the Observatoire du Pic du Midi (TBL) and the Bulgarian National Astronomical Observatory (NAO, Rozhen). Tables 1, 2, 4, 5 and Fig. 7 are only available in electronic form at http://www.aanda.org
Keywords: Astrophysics; Stars: binaries: eclipsing; stars: binaries: general; stars: binaries: spectroscopic; stars: fundamental parameters; stars: variables: general; stars: variables: δ Sct